(untitled) (Medical Forum Monthly, 2026)
Objective: Estimation of antimicrobial activity of AgPNs using green tea leaves extracts against Salmonella typhi. Study Design: True and controlled in vitro laboratory experimental studyPlace and Duration of Study: This study was conducted at the Department of Basic Science, College of Dentistry, Al-Qadisiyah University, Qadisiyah Governorate, Iraq from 10th Aug 2025 to 4th April 2026. Methods: There were several key procedural steps: preparation of the green tea extract, green synthesis of Ag NPs using the extract, and characterization of the resulting Ag nanoparticles by visual color change and UltravioletVisible Spectroscopy (UV-vis). The morphology and particle size of the Ag nanoparticles were determined by SEM. The antibacterial properties of the GT-AgNPs were estimated using the agar well-diffusion test. Results: UV-visible spectroscopy provided key confirmation of AgNP synthesis through a visible color change, arising from collective oscillation of the silver nanoparticles' free electrons in resonance with the incident light wave; this produced a characteristic absorption peak at 440 nm. SEM analysis revealed spherical nanoparticles ranging in size from 20 to 30 nm, with a uniform size distribution and consistent morphology. GT-AgNPs tested at concentrations of 20, 40, and 80 mg/ml produced inhibition zones of 9.5, 14, and 20 mm, respectively, against S. typhi. Conclusion: Green-tea-synthesized Ag nanoparticles show strong, dose-dependent antibacterial activity and represent a promising eco-friendly inhibitor of bacterial growth.